Efektivitas Edukasi Booklet Terhadap Pengetahuan Kepatuhan Minum Obat Lansia Diabetes - Dhesta Pratama; Ahmad Guntur Alfianto; Mizam Ari Kurniyanti (Media Husada Journal Of Nursing Science, 2026)
Abstract Background: Diabetes mellitus is a chronic metabolic disease requiring strict medication adherence, particularly among the elderly. Low health literacy significantly contributes to non-adherence. Educational media such as booklets offer structured visual information suitable for elderly cognitive characteristics.  Objective: This study aimed to determine the effect of booklet-based educational media on elderly knowledge regarding medication adherence in diabetes mellitus. Methods: A quasi-experimental study with a pretest-posttest control group design was conducted at Puskesmas Pakis. A total of 60 elderly patients with type 2 diabetes were selected via purposive sampling and divided into an intervention group (n=30) receiving booklet education and a control group (n=30) receiving standard care. Data were gathered using validated questionnaires and analyzed using the Wilcoxon Signed-Rank Test. Ethical approval was obtained (No. 3261/KEPK/UNIV-NHM/EC/IV/2026).  Results: Before intervention, both groups predominantly exhibited moderate to low knowledge levels. Post-intervention, the intervention group demonstrated a significant increase in knowledge, with 22 respondents (73.3%) reaching the good category, whereas the control group showed less pronounced improvement. The Wilcoxon test yielded a p-value of 0.001 (p < 0.05) for the intervention group, confirming a statistically significant effect. Conclusion: Booklet media significantly enhances elderly knowledge regarding medication adherence in type 2 diabetes mellitus.